Pengaruh Edukasi Audiovisual Terhadap Tingkat Pengetahuan Remaja Tentang Covid-19 di Panti Asuhan Guyup Rukun Kota Bengkulu - Liza Hardiyanti Purnama; Nurhayati Nurhayati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
At the end of 2019 the world was shocked by the latest infection cases caused by Covid-19 which also attacked Indonesia. In humans, the virus causes respiratory issue starting from the common cold to the serious respiratory problems. One of the efforts to prevent the spread of the Covid-19 virus is by promoting health education to increase knowledge by using the audiovisual method. The audiovisual is a media that is focused on the auditory (hearing) and visual (seeing) aspects. The aim of this study was to examine the effect of an audiovisual education on the level of knowledge of teenagers about Covid-19 at the Guyup Rukun Orphanage in Bengkulu. This research was a quasi-experimental approach with a purposive sampling technique. The results showed that there was an increasing level of knowledge of respondents after being given an audiovisual education about Covid-19 from 73.3% (Mean 8.53 SD 1.301) to 93.3% (Mean 10.80 SD 1.612). This finding reflects that promoting health education by using an audiovisual method was effective to increase the level of knowledge of teenagers.